2008
DOI: 10.1111/j.1574-6968.2007.00992.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of class 1 integron abundance in natural environments using real-time quantitative PCR

Abstract: Integrons are bacterial genetic elements capable of capturing and expressing potentially adaptive genetic material. Class 1 integrons constitute the most intensely studied group of these elements to date, mainly due to their well-established role in the acquisition and dissemination of antibiotic resistance genes in clinical environments. However, virtually nothing is known about the distribution or abundance of class 1 integrons outside of the clinical context. Here we develop a SYBR Green-based real-time qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 22 publications
3
82
0
Order By: Relevance
“…Abundance of the intI1 gene (an integrase gene of class 1 integrons), tnpA (a transposase gene of the IS6 family transposons) was quantified on a Bio-Rad CFX96 Real-Time PCR Detection System (Bio-Rad) using the primer sets HS463a/HS464 (Hardwick et al 2008) and tnpA-04F/tnpA-04R (Zhu et al 2013;Wang et al 2014), respectively. The total bacterial 16S rRNA gene was also quantified using the BACT1369F/PROK1492R with the probe TM1389F (Suzuki, Taylor and DeLong 2000).…”
Section: Qpcr Analysis Of the Inti1 Tnpa And Bacterial 16s Rrna Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Abundance of the intI1 gene (an integrase gene of class 1 integrons), tnpA (a transposase gene of the IS6 family transposons) was quantified on a Bio-Rad CFX96 Real-Time PCR Detection System (Bio-Rad) using the primer sets HS463a/HS464 (Hardwick et al 2008) and tnpA-04F/tnpA-04R (Zhu et al 2013;Wang et al 2014), respectively. The total bacterial 16S rRNA gene was also quantified using the BACT1369F/PROK1492R with the probe TM1389F (Suzuki, Taylor and DeLong 2000).…”
Section: Qpcr Analysis Of the Inti1 Tnpa And Bacterial 16s Rrna Genesmentioning
confidence: 99%
“…Integrons possess a site specific recombination system that could capture and express mobile gene cassettes (Heuer, Schmitt and Smalla 2011a), and they were reported to often localize in broad-host-range IncP-1ε plasmids with a wide distribution in agricultural systems that further facilitates their mobility potential (Heuer et al 2012;Jechalke et al 2014c;Wolters et al 2015). The critical roles of integrons in the dissemination of ARGs in environments have been highlighted by cultivation methods and metagenomics approaches (Hardwick et al 2008;Stalder et al 2012;Gillings et al 2015). Class 1 integrons have been extensively studied due to their widespread distribution in Gram-negative bacteria of clinical importance (Stalder et al 2012), and the intI1 genes were reported to be very common in soils and related ecosystems (Gillings et al 2008;Jechalke et al 2014c).…”
Section: Potential For Horizontal Gene Transfer Of Args In Manure-trementioning
confidence: 99%
“…In this context, class 1 integrons retain the gene cassettes that confer adaptive advantages to environmental pressures (Hardwick et al 2008).…”
mentioning
confidence: 99%
“…When the antibiotic resistance gene was not detected in the sample no RQ value was calculated. The function of the endogenous control was to normalise the quantity of DNA in each of the samples (Hardwick et al, 2008), thus ensuring that the RQs of the target antibiotic resistance genes were not biased by differences in the quantity of bacteria or DNA present in the samples. Standard curve generation and delta-delta Ct values were calculated using Applied Biosystems software package.…”
Section: Optimisation Process and Determination Of Multiplex Assay Comentioning
confidence: 99%
“…In order to normalise the data the 16S rRNA gene was chosen. This gene has been previously used as the endogenous control gene in qPCR experiments (Hardwick et al, 2008;Zhang et al, 2000). As the genomes of all bacteria have not as yet been sequenced the exact number of copies of 16S rRNA genes per cell is currently unknown.…”
Section: Introductionmentioning
confidence: 99%